2005
DOI: 10.1303/jjaez.2005.223
|View full text |Cite
|
Sign up to set email alerts
|

High Mortality of Monochamus alternatus Adults Emerging from Pine Logs to Which Non-woven Fabric Strips with Beauveria bassiana Were Applied under Field Conditions.

Abstract: Monochamus alternatus adults emerging from pine logs to which non-woven fabric strips with Beauveria bassiana were applied were reared individually under field or laboratory conditions, and their mortality was investigated. Under field conditions in 2001 and 2002, accumulated mortality on the 15th day after emergence was 95 to 99% of adults emerging from logs with strips, and 68 to 90% of adults emerging from logs with no strips. Under laboratory conditions in 2001 to 2003, the mortality was 84 to 97% for adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Other birds also prey on cerambycid beetles, but according to Yui () these bird species only caught adult beetles when the insects were not hidden, thus only moderately suppressing M. alternatus populations. Available studies have shown in fact that the most important mortality agents for Monochamus are not insectivorous birds but fungi (Kishi, ; Okitsu, Taniwaki, Oota, & Kishi, ; Wang, Xu, Jiang, Zhang, & Yang, ) and parasitic wasps (Naves, Kenis, & Sousa, ). Reptiles have been also reported to predate the vector beetles and reduce the damage from PWN, as reported by Okochi and Kagaya‐Shoda () for the green anole, Anolis carolinensis , in Japan.…”
mentioning
confidence: 99%
“…Other birds also prey on cerambycid beetles, but according to Yui () these bird species only caught adult beetles when the insects were not hidden, thus only moderately suppressing M. alternatus populations. Available studies have shown in fact that the most important mortality agents for Monochamus are not insectivorous birds but fungi (Kishi, ; Okitsu, Taniwaki, Oota, & Kishi, ; Wang, Xu, Jiang, Zhang, & Yang, ) and parasitic wasps (Naves, Kenis, & Sousa, ). Reptiles have been also reported to predate the vector beetles and reduce the damage from PWN, as reported by Okochi and Kagaya‐Shoda () for the green anole, Anolis carolinensis , in Japan.…”
mentioning
confidence: 99%